(untitled) (Academicia Globe: Inderscience Research, 2022)
The essence of the concept of quality are considered in the article. The philosophical aspects of gender equality and its importance in the life of society are discussed. The article emphasizes the importance of equality in human social adaptation to life. There is also a reaction to the study of gender equality in Western and Eastern philosophy.